FORMULASI LEDOK INSTAN YANG DITAMBAHKAN IKAN TONGKOL DAN RUMPUT LAUT [Instant Ledok Formulation by Addition of Frigate Mackerel and Seaweed] - I Ketut Suter; I Made Anom Sutrisna Wijaya; Ni Made Yusa (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
Ledok is a traditional food from Nusa Penida, Bali, in form of non-rice porridge. The main ingredients of ledok are corn and cassava, and other ingredients are peanut, red bean and spinach. These ingredients are locally available. In this study, nutrient content of instant ledok was increased through improving the formulation by adding frigate mackerel and seaweed. The study was conducted in order to find out the best formulation of instant ledok. The experiment was carried out through a Random Block Design, with five formulations of frigate mackerel and seaweed ratio in two replicates. The treatment was ratio of frigate mackerel and seaweed: (1) RI = 0 : 0, (2) R2 = 0 : 30, (3) R3 = 10 : 20, (4) R4 = 20 : 10 and (5) R5 = 30 : 0. The characteristics of instant ledok observed were: sensory characteristics and nutrient contents. The results of the study showed that there was no significant effect of formulation to acceptability of colour and odour, but there were significant effects to taste, texture and general acceptability of instant ledok. The best formulation of instant ledok was formulation R5 with addition of frigate mackerel and seaweed ratio of 30 : 0.The nutrition contents of this instant ledok were 79.60% of water, 0.74% of ash, 3.17% of protein, 3.85% of fat, 12.64% of carbohydrate, 21.15 mg/100 g of vitamin C and 3.43% of vitamin C.